Governing coastal risk: the case of Langebaan's disappearing shoreline - Samuels, Mogammad Yaaseen (Department of Environmental and Geographical Science, 2021)
The coastal zone is the dynamic interface between land and sea and is under immense threat from increasing coastal population and development trends as well as global climate change. Given global and regional sea level rise projections, coastal African countries including South African are highly exposed to climate risks, namely storm surges, flooding and coastal erosion, which particularly impact socio-ecological systems at the local level. The aim of this study is to examine the various technical responses and governance approaches employed by government to address coastal risk along the Langebaan shoreline – a coastal town located in the Western Cape, renowned for its tourism, recreation and scenic attributes. However, the Langebaan shoreline is increasingly at-risk from climate-related sea level rise, compounded by inappropriate coastal development. This research suggests measures to strengthen coastal risk governance (CRG) through exploring stakeholder interpretation of coastal risk as well as understanding the barriers to addressing coastal risk in the context of the Saldanha Bay Municipality (SBM). This study was informed by a review of the legal framework governing coastal risk in South Africa as well as the various technical reports pertaining to addressing coastal erosion in Langebaan. Primary data collection was undertaken through semi-structured interviews. The findings suggest that coastal erosion along the Langebaan shoreline is a complex and multi-faceted human-environmental issue. Furthermore, various reactive steps have been taken in response to Langebaan's eroding shoreline since the 1997 storm, these included hard and soft engineering measures as well as managed retreat. However, the Saldanha Bay Municipality (SBM) remain crippled by lack of institutional capacity and resources to tackle environmental issues like coastal erosion. Therefore, strengthening coastal risk governance (CRG) in under-resourced municipalities like the Saldanha Bay Municipality (SBM) requires improved communication and coordination across all levels of government and with civil society, which in turn will promote long-term strategic thinking and innovative and collective action.